Improving the Guidance Learning (LBB) Consumer Satisfaction in Malang using DANP - TOPSIS method - Andawaningtyas, Kwardiniya; Handamari, Endang Wahyu; Karim, Corina (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2018)
Decision analysis of Multiple Attribute Decision Making (MADM) model is used to assess the performance, not only in a rank but also in a plan of marketing strategy as an effort to increase consumers’ satisfaction by combining DEMATEL-based Analytical Network Process (DANP) method and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. One of the industrial services in the education nowadays is the services of the Guidance Learning (LBB). This article has 3 alternatives to 6 criteria. The questionnaire was distributed to 80 LBB’ students and 55 LBB’ mentors. The result of the dominant criteria affecting customer satisfaction of LBB in Malang by DANP method is the mentor quality. Meanwhile, the TOPSIS result showed that the LBB of Avicenna Education Malang is the best alternative to the marketing strategy..